Phenolic compounds from parasitic Sapria himalayana f. albovinosa and Sapria myanmarensis (Rafflesiaceae) in Myanmar. (December 2020) - Iwashina, Tsukasa; Tanaka, Nobuyuki; Aung, Mu Mu; Devkota, Hari Prasad; Mizuno, Takayuki
Abstract: Three anthocyanins, four flavonols, three aromatic acids and five gallotannins were isolated from Sapria himalayana f. albovinosa in Myanmar. They were identified as cyanidin 3- O -glucoside (1 ), cyanidin 3- O -xyloside (2 ) and peonidin 3- O -glucoside (3 ) (anthocyanins), quercetin 3- O -glucoside (4 ), quercetin 7- O -glucoside (5 ), quercetin 3- O -glucuronide (6 ) and isorhamnetin 3- O -glucoside (7 ) (flavonols), ellagic acid (8 ), gallic acid (9 ) and ethyl gallate (10 ) (aromatic acids), and 1, 2, 4, 6-tetragalloylglucose (11 ), 1, 4, 6-trigalloylglucose (12 ), 1, 2, 6-trigalloylglucose (13 ), 1, 2, 4-trigalloylglucose (14 ) and 1, 6-digalloylglucose (15 ) (gallotannins) by UV, LC-MS, acid hydrolysis, NMR and/or HPLC comparisons with authentic samples. The chemical composition of S. myanmarensis was qualitatively the same with that of S. himalayana f. albovinosa . Phenolic compounds of the Rafflesiaceae species including Sapria, Rafflesia and Rhizanthes were isolated and identified in this survey for the first time. Graphical abstract: Image 1 Highlights: Phenolic compounds of Sapria himalayana f. albovinosa and S. myanmarensis were surveyed. Three anthocyanins, four flavonols, three aromatic acids and five gallotannins were isolated and identified. Phenolic compounds were reported from Rafflesiaceae species including Sapria, Rafflesia and Rhizanthes for the first time.